Study of structural properties and sensing performance of high performance sol-gel synthesized CeTixOy sensing membranes. (10th April 2018) - Pan, Tung-Ming; Tan, Chia-Ying
Abstract: In this paper, we developed a very simple sol-gel spin-coating method to fabricate high performance CeTix Oy sensing membranes for a solid-state electrolyte-insulator-semiconductor (EIS) pH sensor. The surface morphologies, crystal structures, chemical compositions, and elemental depth profiles of the CeTix Oy membranes treated with three different titanium concentrations (0.1, 0.3 and 0.5 M) were studied using a combination of atomic force microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and Auger electron spectroscopy, respectively. The structural properties of the CeTix Oy membranes were corrected with the sensing performances of CeTix Oy EIS pH sensors. The sol-gel synthesized CeTix Oy EIS device prepared at the 0.3 M condition exhibited the best sensing characteristics (pH sensitivity, hysteresis voltage and drift rate) among these conditions. We attribute this behavior to the optimal titanium content in the sensing membrane enhancing the surface roughness CeTix Oy film, increasing the Ce 3+ /Ce 4+ ratio, and forming the stoichiometric Ce2 TiO5 structure. Highlights: High performance CeTix Oy sensing membranes deposited by a simple sol-gel spin-coating method for pH sensors. CeTix Oy EIS device prepared at the 0.3 M condition exhibited the best sensing performance. Optimal Ti content in the sensing membrane can enhance its surface roughness CeTix Oy film and Ce 3+ /Ce 4+ ratio.